JOURNAL OF GOVERNMENT & POLITICS : Conflict Resolution : the Truncated Zoning Arrangement and the Buhari Political Tsunami in Nigeria - Isaac Terungwa Terwase , Asmat-Nizam Abdul-Talib (FISIPOL UMY, 2015)
The Nigerian Fourth Republic ushered in a democratically elected government in 1999 that paved way for the civilians to take over government after a long period of military rule in Nigeria.